Effects of C‐Related Dangling Bonds and Functional Groups on the Fluorescent and Electrochemiluminescent Properties of Carbon‐Based Dots. Issue 17 (23rd February 2018) - Wang, Min; Sun, Ruifen; Wang, Qian; Chen, Lichan; Hou, Linxi; Chi, Yuwu; Lu, Chun Hua; Fu, Fengfu; Dong, Yongqiang
Abstract: Single‐layer carbon‐based dots (SCDs) were chosen as a model to investigate the effect of the C‐related dangling bonds with spin S =1/2 and functional groups on the electrochemiluminescent (ECL) and fluorescent (FL) properties of CDs. The C‐related dangling bonds and functional groups of SCDs were tuned by chemical reduction with NaBH4 . There have several main findings via investigating the ECL and FL properties of SCDs before and after the chemical reduction. First, the FL and ECL of CDs are highly dependent on their concentration, and luminescent resonance energy transfer is observed in ECL studies when the concentration of CDs is high. Second, the ECL activity of CDs is greatly enhanced as the C‐related dangling bonds increase, proving that the ECL of CDs originates from the C‐related dangling bonds. Third, the FL of CDs is the synthesis of the inner FL originated from the contained isolated sp 2 units and the defect FL from the C‐related dangling bonds. The inner FL of CDs is enhanced greatly by removing the carboxyl groups, while the defect FL is increased slightly due to the increased C‐related dangling bonds. We believe this study would promote our understanding in the ECL and FL mechanisms of CDs, advancing the applications of CDs based on their ECL and FL properties. Abstract : Dangling on dots : Chemical reduction removes the carboxyl groups of carbon‐based dots (CDs), forming new C‐related dangling bonds. As a result, both electrochemiluminescence and fluorescent properties of CDs have been changed greatly. The corresponding mechanisms are also discussed.